2017
DOI: 10.14723/tmrsj.42.73
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Sn doped SiO<sub>2</sub> films using SiO<sub>2</sub> and SnO<sub>2</sub> mixture powder target by magnetron sputtering deposition

Abstract: Sn doped SiO2 thin films, which show strong luminescence by UV excitation, were prepared by a sputtering deposition method using a SnO2 and SiO2 powder mixed target. Optical emission spectrum of the plasma using powder target was almost same compared with the conventional sputtering deposition method SiO2 bulk target and Sn atoms were identified in the emission spectrum. XRD and XPS measurements suggest that Sn doped SiO2 thin films can be prepared using SnO2 and SiO2 mixture powder target, and their propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In our previous work, titanium oxide thin films were prepared via sputtering deposition and PLD using a powder target. [26][27][28][29][30][31] These results demonstrated that functional thin films prepared via these methods using a powder target had a quality that was almost the same as those prepared using a bulk target.…”
Section: Introductionmentioning
confidence: 72%
“…In our previous work, titanium oxide thin films were prepared via sputtering deposition and PLD using a powder target. [26][27][28][29][30][31] These results demonstrated that functional thin films prepared via these methods using a powder target had a quality that was almost the same as those prepared using a bulk target.…”
Section: Introductionmentioning
confidence: 72%
“…Powder technique was used in the process of adding powder of Bi to Sn, where the addition process is done based on weight ratios [6]. Tin and bismuth were used in the form of high purity powder up to 99.9%.…”
Section: Experimental Part (Sno 2 ) 1-x (Bi 2 O 3 ) X Thin Filmmentioning
confidence: 99%
“…Figure (6) present the relationship between voltages applied to a LCD cell and the current generated by the optical detector. Curves are divided into three zones: the first extends from A to B where the voltages increase from 0V to 4.7V and the optical current increases slightly and decreases again.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…We previously reported the preparation of functional thin films under various deposition conditions, including high-quality titanium dioxide (TiO 2 ) and zinc oxide (ZnO) films via the PVD method. 15,[21][22][23][24][25][26][27][28][29][30][31][32] We also prepared A6061 thin films via magnetron sputtering 15,16) on a small JIS S25C steel (S25C) substrate. The experimental results indicated that the A6061 film can be prepared on the S25C substrate, and the ∼40 μm thick A6061 film endowed the material with high hydrogen-entry resistance in corrosive environments.…”
Section: Introductionmentioning
confidence: 99%